Effects of Radio Front‐end PLL Phase Noise on GNSS Baseband Correlation. Issue 1 (14th March 2014) - Thombre, Sarang; Tchamov, Nikolay N.; Lohan, Simona; Valkama, Mikko; Nurmi, Jari
ABSTRACT This article presents a study of Global Navigation Satellite System (GNSS) receiver correlation performance in the presence of phase noise (PN) originating from the radio front‐end's phase‐locked loop (PLL). Various constituent PLL sub‐blocks, such as the reference oscillator (RO), phase and frequency detector (PFD), voltage controlled oscillator (VCO), loop filter and frequency dividers contribute to the overall PN of the PLL. The PLL phase noise modeling is covered in detail. Correlation performance of GNSS baseband tracking loops is then calculated as a function of several PLL design parameters, such as the VCO thermal PN, loop filter bandwidth (BW), frequency division ratio (FDR), and the receiver correlator's pre‐detection integration times (PIT). The effects of these parameters on the signal to noise ratio (SNR) of the correlation product are described and simulated. Based on the results of these simulations, we present guidelines for radio front‐end PLL circuit design in order to maintain a minimum baseband correlation performance within the GNSS receiver. Copyright © 2014 Institute of Navigation.